Literasi Artificial Intelligence Berbasis Nilai-Nilai Al-Qur'an dan Hadist - Imam Anas Hadi; Rizka Dewi Khoirunnisa; Ilham Azmi; Dul Muhyi (Najah Bestari, 2026)
The development of Artificial Intelligence (AI) has brought significant changes in various aspects of life, including education, economics, communication, and decision-making. In addition to the various benefits offered, the use of AI also presents ethical challenges such as the dissemination of invalid information, violation of privacy, misuse of technology, and decreased moral responsibility of users. This study aims to examine the concept of Artificial Intelligence literacy based on the values ​​of the Qur'an and Hadith as an ethical basis for utilizing technology responsibly. The study uses a library research method with a normative-philosophical approach and a study of maudhu'i interpretation of the verses of the Qur'an and Hadith related to knowledge, trustworthiness, honesty, tabayyun, responsibility, and benefits. Data are analyzed descriptively and analytically through interpretation of relevant primary and secondary sources. The results show that AI literacy from an Islamic perspective includes not only the ability to understand and use technology, but also the ability to assess, criticize, and utilize AI based on the values ​​of monotheism, trustworthiness, honesty (ṣidq), information verification (tabayyun), justice, and responsibility. These values ​​serve as the foundation for building an ethical, humanistic, and welfare-oriented digital culture. Therefore, integrating AI literacy with the values ​​of the Quran and Hadith can become a relevant Islamic educational paradigm in addressing technological developments while simultaneously developing intelligent, integrated, and morally upright AI users.